Productive Base Sustainability under Climate Change: Theoretical Results and Empirical Evidence - Dimitra Vouvaki; Anastasios Xepapadeas (Kiel Institute for the World Economy (IfW), 2009)
Climate change is one of the most urgent and severe problems on the international agenda and one of the basic factors that determine sustainability conditions. This paper attempts to reveal the connection between productive base sustainability for two large groups of countries, developed and developing, and the state of the environment, which is proxied by the stock of carbon dioxide (CO2) which is mostly responsible for the creation of the global warming phenomenon. Three different policy scenaria for the evolution of global CO2 emissions empirically con.rm the strong association between the state of the environment and productive base sustainability, and provide the foundations for the formulation of sustainability policy.
Keywords: Q01; 330; Productive base sustainability; current change in social welfare; accounting prices; non-optimizing economies; Nachhaltige Entwicklung; Soziale Wohlfahrtsfunktion; Klimaschutz; Kohlendioxid; Luftverunreinigung; Wohlfahrtseffekt; Theorie; Industriestaaten; Entwicklungsländer